Bacterial infection systemically suppresses stomatal density. (10th June 2019) - Dutton, Christian; Hõrak, Hanna; Hepworth, Christopher; Mitchell, Alice; Ton, Jurriaan; Hunt, Lee; Gray, Julie E.
Abstract: Many plant pathogens gain entry to their host via stomata. On sensing attack, plants close these pores to restrict pathogen entry. Here, we show that plants exhibit a second longer term stomatal response to pathogens. Following infection, the subsequent development of leaves is altered via a systemic signal. This reduces the density of stomata formed, thus providing fewer entry points for pathogens on new leaves. Arabidopsis thaliana leaves produced after infection by a bacterial pathogen that infects through the stomata ( Pseudomonas syringae ) developed larger epidermal pavement cells and stomata and consequently had up to 20% reductions in stomatal density. The bacterial peptide flg22 or the phytohormone salicylic acid induced similar systemic reductions in stomatal density suggesting that they might mediate this effect. In addition, flagellin receptors, salicylic acid accumulation, and the lipid transfer protein AZI1 were all required for this developmental response. Furthermore, manipulation of stomatal density affected the level of bacterial colonization, and plants with reduced stomatal density showed slower disease progression. We propose that following infection, development of new leaves is altered by a signalling pathway with some commonalities to systemic acquired resistance. This acts to reduce the potential for future infection by providing fewer stomatal openings.